Electron beam induced strengthening of a short carbon fiber reinforced green thermoplastic composite: Key factors determining materials performance. (June 2019) - Szabó, László; Imanishi, Sari; Tetsuo, Fujie; Nishio, Masaki; Hirose, Daisuke; Tsukegi, Takayuki; Taki, Kentaro; Ninomiya, Kazuaki; Takahashi, Kenji
Abstract: Short carbon fiber reinforced thermoplastic composites are promising materials for creating lightweight structures with short processing time and high potential for recyclability. Our study aimed at preparing composites containing a biobased renewable matrix reinforced with short carbon fibers, and tailoring their mechanical properties by means of electron beam irradiation as a chemical-free green process. Electron beam irradiation of the cellulose propionate matrix brought about competing chain-scission and crosslinking events, the outcome of these processes was finely tuned by directly functionalizing the biopolymer with crosslinking agent. As a result, we found that crosslink formation has a negative effect on the mechanical properties and improvement was only achieved when irradiation was performed on pellets of the neat matrix (∼29% increase in tensile strength). Electron beam treatment strengthens individual carbon fibers embedded in the matrix and renders them more resistive to the shear that develops during further processing eventually yielding longer fibers.